Penerapan Teknik Pengambilan Gambar oleh Director of Photography dalam Pembuatan Video Feature “Makanan yang Terselamatkan, Harapan yang Tersampaikan” - Irfani Nurul Azizah; Teddy K. Wirakusumah; FX. Ari Agung Prastowo (BADAN PENERBIT STIEPARI PRESS, 2025)
In the production process of the video feature “Makanan yang Terselamatkan, Harapan yang Tersampaikan”, the author served as the Director of Photography, responsible for the visual aspects to effectively convey the message of the script. This was achieved through the strategic application of image-taking techniques such as camera angle, shot size, camera movement, and framing. The video feature aims to provide the public with an overview of the issue of food waste in Bandung, as well as the food rescue activities carried out by Food Bank Bandung. This work is expected to raise public awareness about the importance of managing food wisely to prevent it from going to waste. The applied image-taking techniques successfully enhance the role of this video feature as an effective medium for delivering information.